2008
DOI: 10.1002/dvdy.21542
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and developmental biology of the hemangioblast

Abstract: The hemangioblast hypothesis was proposed a century ago. The existence of hemangioblasts is now demonstrated in mouse and human embryonic stem cell (ESC) -derived embryoid bodies (EBs), in the mouse and zebrafish gastrula, and in adults. The hemangioblast is believed to derive from mesodermal cells, and is enriched in the Bry ؉ Flk1 ؉ and Flk1 ؉ Scl ؉ cell populations in EBs and in the posterior primitive streak of the mouse gastrula and in the ventral mesoderm of the zebrafish gastrula. However, recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 197 publications
(227 reference statements)
0
62
0
Order By: Relevance
“…One such fate decision, which is poorly understood, concerns the choice between hematopoietic and blood cell differentiation in hematopoietic organs where these cells develop in close association. The co-specification of these lineages is supported by a large body of evidence in all vertebrates, including chick, mouse, zebrafish and Xenopus (reviewed by Ferguson et al, 2005;Red-Horse et al, 2007;Xiong, 2008). In the hematopoietic regions of Xenopus embryos, for example, a combination of lineage tracing and gene expression experiments showed that both lineages pass through a progenitor state in which they co-express blood and endothelial genes (Ciau-Uitz et al, 2000;Walmsley et al, 2002).…”
Section: Rspo3 Regulates Hematopoietic/angioblast Fate In Xenopusmentioning
confidence: 99%
See 1 more Smart Citation
“…One such fate decision, which is poorly understood, concerns the choice between hematopoietic and blood cell differentiation in hematopoietic organs where these cells develop in close association. The co-specification of these lineages is supported by a large body of evidence in all vertebrates, including chick, mouse, zebrafish and Xenopus (reviewed by Ferguson et al, 2005;Red-Horse et al, 2007;Xiong, 2008). In the hematopoietic regions of Xenopus embryos, for example, a combination of lineage tracing and gene expression experiments showed that both lineages pass through a progenitor state in which they co-express blood and endothelial genes (Ciau-Uitz et al, 2000;Walmsley et al, 2002).…”
Section: Rspo3 Regulates Hematopoietic/angioblast Fate In Xenopusmentioning
confidence: 99%
“…The close association of hematopoietic and angioblastic cell development is probably due to the fact that both cell types derive from a mesodermal hemangioblast precursor, for which there is good evidence in zebrafish, Xenopus, chick, mouse and humans (Eichmann et al, 1997;Kennedy et al, 1997;Choi et al, 1998;Jaffredo et al, 1998;Nishikawa et al, 1998;Jaffredo et al, 2000;Walmsley et al, 2002;Huber et al, 2004;Ferguson et al, 2005;Vogeli et al, 2006;Kennedy et al, 2007) (reviewed by Red-Horse et al, 2007;Xiong, 2008) [but see Ueno and Weissman (Ueno and Weissman, 2006)]. …”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic cells and vascular endothelial cells share a common precursor, the hemangioblast (Xiong, 2008). In the first stage of blood vessel development, vascular endothelial cells are differentiated from the hemangioblast and form a vascular structure, with the main blood vessels being formed.…”
Section: Induction Of Vascular Endothelial Cells From Undifferentiatementioning
confidence: 99%
“…7 Reconciling these apparently contradictory results is difficult but may relate to the link between vascular and hematopoietic development. [8][9][10][11] Vitamin A-deficient quail embryos display abnormal vascular development, 7 whereas Raldh2 knockout mice have impaired formation of yolk sac hemogenic endothelium and decreased hematopoietic progenitors in the absence of RA. 6 In addition, Raldh2 deletion is lethal by embryonic day 10.5 in the mouse because of a complex cardiac looping defect, 12 limiting the evaluation of hematopoiesis in these mutants.…”
Section: Introductionmentioning
confidence: 99%